90
Just plug in 30 for n in 3n-1. The answer is 89.
Say if you had the pattern 15 20 25 30 35 40 45 50 To find the nth term you have to see what the gap between the numbers is. In our case this is 5. Then you have to find out what the difference between the gap and the first number. In this sequence it is 10. So your answer would be..... 5n+10 That's how you find the nth term.
> since the value rises by nine at each step and the first term is 12 the formula for > the nth term is: 12+(n-1)*9 Which simplifies to Sn = 9n + 3
You can see that all the numbers go up by 7. This means that the first part of the nth term rule for this sequence is 7n. Now, you have to find out how to get from 7 to 3, 14 to 10, 21 to 17 ... this is because we are going up in the 7 times table. To get from the seventh times table to the sequence, you take away four. So the answer is : 7n-4
6n+10
9 ,16 ,23, 30 We note that there is a difference of '7' between terms. So the first part of the 'nth' term is 7n. Note the '7' becomes multiple. Next we need to find the constant 'c' So taking the first term (n = 1) we write. 7n + c = 9 7(1) + c = 9 7 + c = 9 c = 2 So the 'nth' term is '7n + 2' To verify , try the 3rd term n= 3 then answer should be '23'. 7(3) + 2 = 21 + 2 = 23 As required.
t(n) = 5 - 7n for n = 1, 2, 3, ... The difference between each term is -7, therefore the nth term will be: t(n) = -2 + -7 × (n - 1) = -2 + 7n + 7 = 5 - 7n
We note that the numbers rise by addition of ;7;7 between terms. Hence we can write 7n . The first term( n- 1) is '9' So we can write 7(1) + c = 9 7 + c = 9 c = 2 So the nth term becomes 7n + 2
Clearly here the nth term isn't n25.
90
To find the nth term of a sequence, we first need to identify the pattern or rule governing the sequence. In this case, the sequence appears to be increasing by consecutive odd numbers: 10, 14, 18, 22, and so on. To find the nth term, we can use the formula for the nth term of an arithmetic sequence: a_n = a_1 + (n-1)d, where a_n is the nth term, a_1 is the first term, n is the position of the term, and d is the common difference. In this sequence, a_1 = 6 and the common difference is 10. Therefore, the nth term can be expressed as a_n = 6 + (n-1)10.
Well, honey, if the nth term is 3n-1, then all you gotta do is plug in n=30 and do the math. So, the 30th term would be 3(30)-1, which equals 89. There you have it, sweet cheeks, the 30th term of that sequence is 89.
30
Just plug in 30 for n in 3n-1. The answer is 89.
3 x 10(n-1)
n(n+1)